2020
DOI: 10.1111/are.15074
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriological, molecular, and pathological studies on the Gram‐positive bacteria Aerococcus viridans and Enterococcus faecalis and their effects on Oreochromis niloticus in Egyptian fish farms

Abstract: In this field study, two private Oreochromis niloticus fish farms in El Fayoum and El Sharkia governorates showed signs of septicaemia, with a mortality of 20%–25% between autumn 2018 and summer 2019. Postmortem examination of affected fish revealed loose scales, ulceration in the dorsal part of the head, petechial haemorrhages on the body surfaces, unilateral exophthalmia, and corneal opacity together with congested blood vessels of nearly all fleshy portions of the body fins. Internal examination of the visc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…For example, in 2018 and 2019 disease caused by infection with A. viridans caused extensive financial losses in the Egyptian tilapia aquaculture sector with morbidity and mortality rates of 20-25%. Research has shown that mortality in fish purposively infected with A. viridans can be as high as 91% by 6 days after injection (Elgohary et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…For example, in 2018 and 2019 disease caused by infection with A. viridans caused extensive financial losses in the Egyptian tilapia aquaculture sector with morbidity and mortality rates of 20-25%. Research has shown that mortality in fish purposively infected with A. viridans can be as high as 91% by 6 days after injection (Elgohary et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…extensus ectoparasites. Cells, especially hepatocytes from different fish, typically evoke various tissue responses against stresses, including those from bacterial infections (Elgohary et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, some Enterococcus sp. have been isolated from both healthy and infected fish species, causing streptococcallike infections in Yellowtail (Seriola quinqueradiata) in Japan, tilapia (Oreochromis niloticus) in Egypt, catfish (Clarias batrachus) in Bangladesh and common carp (Cyprinus carpio) in Thailand (Elgohary et al, 2020;Nieto et al, 1995;Petersen & Dalsgaard, 2003;Plumb & Hanson, 2010;Rahman et al, 2017). (He et al, 2015;Kaewngernsong et al, 2019).…”
mentioning
confidence: 99%
“…The diseased fish showed congested gills and abdomen, a swollen gall bladder and a severe diffusion in the liver. A. viridans infections have been subsequently reported in Indonesian, 278 and in Egyptian tilapia farms, 279,280 always in combination with other bacteria. In Indonesia, the bacterium was isolated in a screening of water from a tilapia pond and in faeces of tilapia, and was identified by biochemistry.…”
Section: Aerococcosis (Aerococcus Viridans)mentioning
confidence: 99%
“…In Indonesia, the bacterium was isolated in a screening of water from a tilapia pond and in faeces of tilapia, and was identified by biochemistry 278 . In Egypt, the bacterium was isolated as one of 17 in a multibacterial infection of wild caught tilapia from the Nile River, 279 and it was isolated from diseased tilapia from two tilapia farms, in combination with Enterococcus faecalis , 280 and the A . viridans were identified by molecular methods, like 16SrRNA typing.…”
Section: Reviewmentioning
confidence: 99%